Future of regional cooperation in Asia and the Pacific - Susantono, Bambang; Park, Cyn-Young (Asian Development Bank, 2020)
This book reviews progress with regional cooperation and integration in Asia and the Pacific and explores how it can be reshaped to achieve a more resilient, sustainable, and inclusive future. Consisting of papers contributed by renowned scholars and Asian Development Bank staff, the book covers four major areas: public goods, trade and investment, financial cooperation, and regional health cooperation. The book emphasizes how the region can better leverage regional integration to realize its vast potential as well as overcome challenges such as the coronavirus disease (COVID-19) pandemic.